Waste implications from minor impurities in European DEMO materials. (29th May 2019) - Gilbert, M.R.; Eade, T.; Rey, T.; Vale, R.; Bachmann, C.; Fischer, U.; Taylor, N.P.
Abstract: Waste-production predictions for the future demonstration fusion power plant (DEMO) are necessary to produce an accurate picture of the likely environmental and economic costs of radioactive waste disposal at end-of-life. An integrated simulation process combining Monte-Carlo neutron transport simulations, inventory calculations, and extensive and reproducible post-processing algorithms has been used for the evolving European DEMO designs to quantify the time-varying mass inventories in different waste classes for individual regions and components of the reactor vessel, as well as for the reactor as a whole. Waste categories based on UK and French regulations reveal that minor impurities contained in structural steels, particularly Eurofer, as well as in functional materials such as tungsten, and beryllium, can have a significant impact on their waste classification prospects. Predictions for current European DEMO concepts suggest that there may be an issue in disposing of fusion structural-steel waste as low-level waste (LLW) in near-surface repositories. Detailed analysis of the subtleties of these predictions, particularly with regard to the production of long-lived radionuclides such as 14 C and 94 Nb, reveal that the threshold for acceptance as LLW is only just exceeded in some situations. Several mitigation approaches are discussed in this context. The computational framework developed for these assessments can be rapidly and continuously applied to the maturing DEMO design, helping to guide design choices to mitigate long-lived waste production and ensure that most waste becomes LLW or better within a few decades.